Halibut Jackson - Lucas, David, 1966- (New York : Knopf : Distributed by Random House, 2004)
Halibut Jackson is so shy that he makes special outfits to blend in wherever he goes, but the clothes he wears to a party at the palace only make him stand out.
Keywords: Bashfulness -- Fiction; Clothing and dress -- Fiction; Individuality -- Fiction